Pengaruh Lifestyle, Keunikan Produk, Dan Green Product Terhadap Keputusan Pembelian Produk Fashion Ecoprint (Studi Kasus Pada Konsumen Griya Madukara Malang) - Nuril Zayyidah; Nur Ajizah (LPPM Universitas Buddhi Dharma, 2025)
An increasingly environmentally conscious lifestyle encourages consumers to be more selective in choosing fashion products. Ecoprint fashion products, with unique designs that use natural dyes from plants, offer uniqueness that other fashion products do not have. This uniqueness attracts consumers who are looking for exclusivity. In addition, as an environmentally friendly product, ecoprint products attract consumers who are aware of environmental problems and desires. The combination of an environmentally conscious lifestyle, product uniqueness and status as an environmentally friendly product makes ecoprint fashion products an attractive choice for consumers who prioritize desire and uniqueness in their purchase decisions. The purpose of this study is to measure the influence of Lifetyle, Product Uniqueness and Green Product on the Purchase Decision of ecoprint fashion products. The population in this study is Griya Madukara Malang consumers with a sample of 100 respondents taken by the purposive sampling method. The analysis method used is multiple linear regression analysis. To obtain the test results in this study, a classical assumption test was carried out, namely a normality test, a multicollinearity test, a heterokedasticity test, an autocorrelation test, and then a hypothesis test was carried out using the Statistical Package For the Social Sciences (SPSS). The results of this study show that simultaneously the variables Lifestyle, Product Uniqueness and Green Product have a positive effect on the variables of Purchase Decision.